DAYA HAMBAT EKSTRAK LIDAH BUAYA (Aloe barbadensis Miller) TERHADAP PERTUMBUHAN BAKTERI Staphylococcus aureus SECARA IN VITRO - Pramesti Indah Prabasari; I M Sumarya; N.K.A. Juliasih (UNHI Press, 2019)
Aloe vera (Aloe barbadensis Miller) contains anthraquinone compounds, flavonoids and saponins which are thought to have antibacterial effects so as to inhibit bacterial growth. The purpose of the study was to determine the inhibitory power of Aloe barbadensis Miller on the growth of Staphylococcus aureus bacteria. The pure experimental study was conducted with The Randomized Posttest Only Control Group Design using six (6) treatments, namely aloe vera extract with a concentration of 25%, 50%, 75%, 100%, Chloramphenicol 30 mcg antibiotics as a positive control, and sterile aquadest as a control negative for Staphylococcus aureus bacteria grown on Mueller Hinton media. After being treated, it was incubated for 24 hours and measured its inhibitory power. The growth inhibition data of Staphylococcus aureus bacteria in the form of inhibition zone diameter was analyzed statistically by Kruskal Wallis test, at the level of confidence α = 0.05. The results showed that the average inhibitory effect of Aloe vera extract on the growth of Staphylococcus aureus bacteria in concentrations of 25%, 50%, 75% and 100% were 0 ± 0 mm; 7.125 ± 0.1250 mm; 8.375 ± 0.23936 mm; and 9.0 ± 0.40825 mm. Based on the results of the study concluded that aloe vera extract can inhibit the growth of Staphylococcus aureus bacteria. The higher the concentration of Aloe vera extract the greater the inhibitory effect on the growth of Staphylococcus aureus bacteria.